GTP binding to the ROC domain of DAP-kinase regulates its function through intramolecular signalling - Carlessi, Rodrigo; Levin-Salomon, V.; Ciprut, S.; Bialik, S.; Berissi, H.; Albeck, S.; Peleg, Y.; Kimchi, A. (2011)
Death-associated protein kinase (DAPk) was recently suggested by sequence homology to be a member of the ROCO family of proteins. Here, we show that DAPk has a functional ROC (Ras of complex proteins) domain that mediates homo-oligomerization and GTP binding through a defined P-loop motif. Upon binding to GTP, the ROC domain negatively regulates the catalytic activity of DAPk and its cellular effects. Mechanistically, GTP binding enhances an inhibitory autophosphorylation at a distal site that suppresses kinase activity. This study presents a new mechanism of intramolecular signal transduction, by which GTP binding operates in cis to affect the catalytic activity of a distal domain in the protein. © 2011 European Molecular Biology Organization.